Harmonic Function For Which The Second Dilatation is Alpha-Spiral - Duman Yavuz, Emel; Aydoğan, Melike; Kahramaner, Yasemin; POLATOĞLU, YAŞAR (Springer International Publishing Ag, Gewerbestrasse 11, Cham, Ch-6330, Switzerland, 2012)
Let f = h + (g) over bar be a harmonic function in the unit disc . We will give some properties of f under the condition the second dilatation is alpha-spiral
Keywords: harmonic functions; growth theorem; distortion theorem; coefficient inequality; harmonik fonksiyonlar; büyüme teoremi; bozulma teoremi; katsayı eşitsizliği